Pembelajaran Sastra di Sekolah - Arif Hidayat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Literature learning can be used as studentâ€™s self development, in form interest and talent realization. This implemented with reading, writing, and appreciation activity. From these three activity, literature learning at school can reach there main learning competence, namely affective, cognitive, and psychomotor competence. But literature learning still not reaches optimal outcome, explicit from lack of Indonesia writer that â€œbornâ€ from literary faculty.Â Â